O Passado que não passa: memória, história e exílio na ficção de Edna O'Brien - Abrantes, Elisa Lima (2010)
The purpose of this dissertation is to investigate the different constructions of reality in three of Edna O Brien s works Mother Ireland (1976), House of Splendid Isolation (1994) and The Light of Evening (2006) while seeking to evince, through the critical analysis of these texts, how historical metanarratives which suggest that the colonial past gave way to the modernization and internationalization of Ireland are problematized. By pointing out the relation between the colonial past and the neocolonial present, and suggesting that the national question has not been resolved, O Brien s work offers valuable interpretative tools for understanding the Irish experience. Through the imbrication of history, memory, and fiction, and an inter-discursive reading of the works selected for analysis, I have sought to establish a discussion of the representations of identity, nation, and exile in the author s work. Finally, the